Cooperation networks of ambulatory health care providers: exploration of mechanisms that influence coordination and uptake of recommended cardiovascular care (ExKoCare) : a mixed-methods study protocol - Arnold, Christine; Hennrich, Patrick; Koetsenruijter, Jan; Lieshout, Jan van; Peters-Klimm, Frank; Wensing, Michel (BMC family practice, 2020)
As the number of elderly and multimorbid patients increases, healthcare has become more complex. This requires good coordination of treatment and care given the various health care professionals involved (e.g. general practitioners, medical specialists, physicians’ assistants). Lack of coordination jeopardizes seamless, evidence-based treatment and care, and eventually reduces clinical effectiveness. The aim of the study is a) to describe and explore information transfer and interprofessional collaboration in ambulatory cardiac care, b) to describe and explore the role of provider networks from the perspective of patients and providers, focusing on healthcare coordination and the uptake of recommended practices.
Gesehen am 18.08.2020